Unlocking faba bean (Vicia faba L.) potential: How cattle manure and fertilizer boost yields in Kaffa Zone, South-Western Ethiopia - Isreal Zewide; Asrat Ademe (Heliyon)
This study aimed to optimize faba bean (Vicia faba L.) productivity in Adiyo, southwest Ethiopia, by evaluating the influence of cattle manure (CAM) and blended nitrogen phosphrous sulfur and boron (NPSB) fertilizer rates during the 2023 crop season. Faba bean, a crucial grain legume in Ethiopia, was grown in Alargeta and Boka locations of Adiyo Woreda, Kaffa Zone, and Southwestern Ethiopia. The experiment comprised factorial combinations of four cattle manure (CAM) levels (control., 2.5, 5, 7.5 ha-1) and four NPSB fertilizer levels (control., 50, 100, 150 kg ha−1) arranged in a Randomized Complete Block Design (RCBD) with three replications. Statistical analysis revealed highly significant combined effects of cattle manure (CAM) and blended nitrogen phosphrous sulfur and boron (NPSB) fertilizer on faba bean harvest index at Alargeta, while Boka exhibited no significance. The highest harvest index (52.5 % and 49.8 %) resulted from cattle manure (CAM) 5 t ha−1 + 150 kg ha−1 nitrogen phosphrous sulfur and boron (NPSB) fertilizer, equivalent to cattle manure (CAM) 7.5 t ha−1 + 150 kg ha−1 NPSB at Boka. Conversely, the lowest values (42.8 % and 41.9 %) were observed in control treatments at Alargeta and Boka. cattle manure (CAM) 5 t ha−1 + nitrogen phosphorus sulfur and boron (NPSB) 150 kg ha−1 exhibited superiority in various parameters, such as the number of branches, plant height, grain yield, hundred seed weight, pods per plant, pod length, and seeds per pod at both locations. This treatment yielded favorable Marginal Rates of Returns (MRRs) of 2595.1 % and 1545.3 %, surpassing the acceptable minimum of 100 %, while control treatments yielded lower net benefits (132,280 and 121,430 ETB ha−1). In conclusion, the integrated application of cattle manure (CAM) 5 t ha−1 with 150 kg ha−1 nitrogen phosphorous sulfur and boron (NPSB) emerged as an economically viable strategy for enhancing faba bean productivity in the study areas, suggesting its potential applicability in similar agro-ecological settings.